Pengaruh Kebijakan Rantai Pasok, Kapabilitas Logistik, terhadap Integrasi Logistik dan Keunggulan Bersaing pada UKM di DIY Yogyakarta - Anandia Deni Safitri; Mochamad Nasito (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2022)
This study discusses the influence of supply chain policies, logistical capabilities, on logistics integration and competitive advantage in SMEs in DI Yogyakarta. The measurement method uses multiple linear regression analysis to determine supply chain policies, logistics capabilities, logistics integration and competitive advantage in SMEs in DI Yogyakarta. The sample data was obtained from the questionnaire method. The sample used in this study was SME DI Yogyakarta who had filled out the questionnaires distributed. The number of questionnaires filled in and sampled were 30 SMEs. Multiple regression results show that supply chain policies have a significant positive effect on logistics integration. Logistics capability has a significant positive effect on logistics integration. Supply chain policies have a positive and significant impact on competitive advantage. However, logistics capability has no significant effect on competitive advantage as well as logistics integration which has no significant effect on competitive advantage.